Effectiveness of Management and Development of Markets Bandar Kediri City Based on Regional Regulation of Kediri City Number 5 Year 2013 in Maslahah Mursalah Perspective - Umi Azizah Tahta Almuna; Tutik Hamidah (Al-Balad: Journal of Constitutional Law, 2019)
In implementing regional regulations, it has not been fully implemented effectively. Legal factors, law enforcement factors, facilities and infrastructure or facilities, and community factors are obstacles in overcoming violations in traditional market areas. For example in the Bandar market area, the use of buildings provided for traders is not optimal, as evidenced by the emergence of traders who sell on the sidewalk. So that this condition results in a lack of comfort for market users and road users in their activities. Slum, dirty is something that will definitely be found in the market, this condition has a negative impact on the development of the market itself. The formulation of the selected problem is How is the effectiveness of Article 18 of the Regional Regulation of Kediri City Number 5 of 2013 concerning the Arrangement and Development of Traditional Markets, Shopping Centers and Modern Store in Bandar Market Kediri City? How is Maslahah Mursalah's review of the traditional market Bandar area in Kediri City Market after the enactment of Regional Regulation Number 5 of 2013? This research is empirical legal research using a sociological juridical approach by describing in depth about the object under study. And the data collection methods used are interviews (interviews), observation, and documentation. The results showed that the effectiveness of Regional Regulation No. 5 of 2013 concerning the Arrangement and Development of the Bandar Kediri City Traditional Market was not yet effective. This is due to the non-compliance of traders selling merchandise on the sidewalk. Whereas the Regional Regulation according to Maslahah Mursalah's perspective has provided benefits where the purpose of the establishment of Regional Regulations brings benefits to lawmakers, law enforcers, and those who implement the law.